Antiulcer Effect of Genus Symphytum L. and Portulaca oleracea L. as Investigated on Experimental Animals - El-Sayed H. Bakr; Amal Al-Ghamdi; Reham Al-Amri; Muna Al-Otaibi; Nada Al-Saad; Ghala Al-Matrafi; Ziad T. Kishmira; Firas Azzeh; Areej A. Almuraee (Journal of Nutrition and Metabolism)
Peptic ulcer disease (PUD) occurs when open sores, or ulcers, form in the stomach or first part of the small intestine caused by bacterial infection (H. pylori) and/or nonsteroidal anti-inflammatory drug (NSAID) use. This study was conducted to evaluate the antiulcer effect of some plants including genus Symphytum L., and Portulaca oleracea L. on aspirin-induced acute gastric ulcer in rats. Sixteen male albino rats (200–210 g b.wt. each) were divided into 4 groups, 4 rats each, one of them left as the control −ve group while the other 3 groups orally administered with aspirin at a dose of 200 mg/kg b.wt., for gastric ulcer induction, one of them left as control +ve and the rest 2 groups were orally administered with genus Symphytum L. and Portulaca oleracea L. at a dose of 100 mg/kg b.wt., each. for seven consecutive days. Body weight gain (BWG), the length of gastric ulcer, the volume of gastric juice, the total acidity of gastric juice, and blood sample were assessed. The results showed that orally administered with genus Symphytum L. and Portulaca oleracea L. significantly reduced the length of gastric ulcer, gastric juice volume, and total acidity of gastric juice, in addition to decreasing total cholesterol (TC), triglyceride (TG), aspartate aminotransferase (AST), alanine aminotransferase (ALT), alkaline phosphatase (ALP), RBC, WBC, HGB, and PLT. No significant changes were observed in the pH of gastric juice among treated groups. Moreover, in comparison to Portulaca oleracea L., genus Symphytum L. showed preferable results. Accordingly, genus Symphytum L. and Portulaca oleracea L. could be used as plants as curative agents against gastric ulcer in experimental rats.